Adrenal cortical and chromaffin stem cells: Is there a common progeny related to stress adaptation? - Steenblock, Charlotte; de Celis, Maria F. Rubin; Androutsellis-Theotokis, Andreas; Sue, Mariko; Delgadillo Silva, Luis F.; Eisenhofer, Graeme; Andoniadou, Cynthia L.; Bornstein, Stefan R. (Elsevier, 2017)
The adrenal gland is a highly plastic organ with the capacity to adapt the body homeostasis to different physiological needs. The existence of stem-like cells in the adrenal cortex has been revealed in many studies. Recently, we identified and characterized in mice a pool of glia-like multipotent Nestin-expressing progenitor cells, which contributes to the plasticity of the adrenal medulla. In addition, we found that these Nestin progenitors are actively involved in the stress response by giving rise to chromaffin cells. Interestingly, we also observed a Nestin-GFP-positive cell population located under the adrenal capsule and scattered through the cortex. In this article, we discuss the possibility of a common progenitor giving rise to subpopulations of cells both in the adrenal cortex and medulla, the isolation and characterization of this progenitor as well as its clinical potential in transplantation therapies and in pathophysiology.